Development of a nanosatellite attitude control simulator for ground-based research - Newton A; Hill ED; Gadsden SA; Biglarbegian M (SPIE, the international society for optics and photonics, 2022)
The work presented in this paper details the design, development, and functional verification of a Nanosatellite Attitude Control Simulator (NACS). The NACS consists of a mock 1U CubeSat (MockSat), tabletop air-bearing, and automatic balancing system (ABS). The MockSat employs a reaction wheel array to exchange momentum with the rigidly attached air bearing platform, and an inertial measurement unit to obtain state estimates. The ABS tunes the center of gravity to coincidence with the center of rotation, in an attempt to minimize gravitational torques. Simulation and experimental results validate the theoretical basis of the PD controller, as well as the implementation of the numerous software and hardware modules. This experimental setup can be used by future researchers to benchmark, test, and compare different estimation and control strategies.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 4010 Engineering Practice and Education